1986
DOI: 10.1017/s0003356100002579
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of wilted and unwilted silages by lactating cows and the influence of changes in the protein and energy concentration of the supplement offered

Abstract: Twenty-four lactating British Friesian cows were used in a four-period partially balanced change-over design experiment to evaluate eight treatments consisting of two silage types (wilted and unwilted), each offered in addition to supplements containing both two crude protein (CP) levels (160 and 210 g/kg fresh weight) and two energy levels (10-8 and 12-9 MJ metabolizable energy (ME) per kg fresh weight) obtained by including 100 g spray-dried tallow per kg, in a 2 x 2 x 2 factorial arrangement. All supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
6
5
2
Order By: Relevance
“…The resulting silages had good fermentations and the major differences in chemical compositions were higher ash, higher pH, lower crude fibre and lower organic acid concentration with the wilted than the unwilted material, all being in line with other data reported following wilting (Marsh, 1979;Gordon, 1980a and b;Castle and Watson, 1982). However, a consequence of this has been that the ME concentrations of the silages (derived assuming methane energy as 0-08 of GE) indicated only a marginally higher ME with the unwilted than the wilted silage whereas other studies from this Institute and elsewhere have generally indicated a much higher ME with the unwilted material (Gordon and Peoples, 1986). This is contrary to most other published data (Zimmer and Wilkins, 1984) and cannot be readily explained.…”
Section: Effect Of Wilting Prior To Ensilingsupporting
confidence: 89%
See 4 more Smart Citations
“…The resulting silages had good fermentations and the major differences in chemical compositions were higher ash, higher pH, lower crude fibre and lower organic acid concentration with the wilted than the unwilted material, all being in line with other data reported following wilting (Marsh, 1979;Gordon, 1980a and b;Castle and Watson, 1982). However, a consequence of this has been that the ME concentrations of the silages (derived assuming methane energy as 0-08 of GE) indicated only a marginally higher ME with the unwilted than the wilted silage whereas other studies from this Institute and elsewhere have generally indicated a much higher ME with the unwilted material (Gordon and Peoples, 1986). This is contrary to most other published data (Zimmer and Wilkins, 1984) and cannot be readily explained.…”
Section: Effect Of Wilting Prior To Ensilingsupporting
confidence: 89%
“…Zimmer and Wilkins (1984) from the Eurowilt studies have reported a mean proportionate depression in milk yield over four studies of 0-02 following wilting. This set of data is therefore not in line with that reported earlier (Gordon and Peoples, 1986) or by Zimmer and Wilkins (1984) which suggested no effects of wilting on the efficiency of MEP use for milk production nor the calorimetric data presented by Unsworth and Gordon (1985) which indicated no effect of wilting on efficiency of ME utilization for milk production. The explanation for the difference between the results of the present investigation with those reported previously lies in the very much greater increase in silage intake, and hence GE intake, and the higher digestibility of the wilted silage based diets in the present study.…”
Section: Effect Of Wilting Prior To Ensilingcontrasting
confidence: 87%
See 3 more Smart Citations